Bioaugmentation on humification during co-composting of corn straw and biogas slurry. (April 2023) - Cao, Zhenglei; Deng, Fang; Wang, Ruxian; Li, Jiabao; Liu, Xiaofeng; Li, Dong
Graphical abstract: Highlights: 2.5 L biogas slurry can be consumed by the co-composting with 1 kg straw. Bioaugmentation enhanced the Maillard and polyphenol humification pathways. The strengthening effect of bacteria was more significant than that of biochar. Bioaugmentation reduced the loss of C and N by promoting the formation of CN of HA. The humified co-compost had nutrient slow-release effect in agricultural production. Abstract: In order to increase the nutrients and humic acid (HA) contents of corn straw (CS) derived organic fertilizer and recover resources from biogas slurry (BS) simultaneously, the co-composting of CS and BS was carried out with the addition of biochar and microbial agents including lignocellulose degrading and ammonia assimilating bacteria. The results showed that 1 kg straw could treat 2.5 L BS by recovering nutrients and bio-heat introduced evaporation. The bioaugmentation strengthened both the polyphenol and Maillard humification pathways by promoting the polycondensation of precursors (reducing sugars, polyphenols, and amino acids). HA obtained in the microbial-enhanced group (20.83 g/kg), biochar-enhanced group (19.34 g/kg), and combined-enhanced group (21.66 g/kg) were significantly higher than that in the control group (16.26 g/kg). The bioaugmentation achieved directional humification and reduced the loss of C and N by promoting the CN formation of HA. The humified co-compost had nutrient slow-release effect in agricultural production.